Principles of Entrepreneurship (ENT530): Case Study: Company Analysis: Pastelsey / Afifah Nazaruddin - Nazaruddin, Afifah; Abu Hanifah, Norfatihah; Kasmiri, Nur Fathehah Farhanah; Samsul Nizal, Nur Salsabila; Farhanah, Dea Shika; Samsor, Muhammad Izzuddin (2021)
The company that has been selected as our case study is Pastelsey Sdn. Bhd. It was established on May 2017 and their headquarters is located in Shah Alam, Selangor. The company currently operates in the product and services sector. Pastelsey is one of the online business that offers high quality telephones and telecommunication equipment with Apples brands. The services that they provide are direct sales or walk-in and post by courier. Pastelsey promote their products by using social media like Facebook and Instagram as their main platform. That is because their target audience is youngster and student that using social media. Mostly of the resellers are student, so using social media will ease them to promote their products and gain more customers. Nowadays, every business will face a lot of challenges and problems. From this case study, we can derive the problems that companies often face. Company performance is an important element in attracting customers to use the services provided by the company. In addition, the input that can be obtained from this study is to know about the organizational structure, products, business, marketing and operating strategy of this company. Lack of marketing strategy will make this company less known by other customers. Further, the management system should be improved to improve the performance of the company. All these weaknesses can be identified with SWOT Analysis by analyzing the strengths, weaknesses, opportunities and threats of the company. Therefore, all the problems that can affect the performance of the project can be solved. At the end of this case study, we will discuss and provide some suggestions or recommendations to solve the problems faced by the company